Learning Networks: an Alternative to Traditional Methods of Managing Organizational Change. What We Can Learn from the Experience of the National Society of French Railways - David Autisier; E.V. Pachtchenko-de Préville; Thierry Raynard (Управление)
In an unstable economic environment, organizations and companies must constantly adapt and innovate to remain competitive. To innovate and develop its ability to adapt, the organization (company) must release the power of the thoughts and actions of its employees, it must become a learning organization. Learning networks are one of the forms of the learning organization and an alternative to traditional methods of managing organizational change. Learning networks can be used while driving organizational change and should involve the largest number of participants and introduce change whilst satisfying the needs of customers, employees and the company. In this article, we will present the keys to operating learning networks and some key results achieved through learning networks within the National Society of French Railways, where these networks have been in use since 2007.